GOOGLE SITES: DEVELOPMENT OF 3D CAD TUTORIAL VIDEO FOR CLASS XI AT SMKN 1 BLITAR - Azizah, Ambar Isna; Herwanto, Heru Wahyu (Jurnal Dinamika Vokasional Teknik Mesin, 2024)
This development research is using the ADDIE model (analysis, design, development, implementation, evaluation) with a quantitative approach. The discussion of the research results is limited to the development stage until the product feasibility validation test. The data collection instrument of this research is a questionnaire with a Likert scale (1-4). The development of 3D drawing video tutorial media using the ADDIE model provides good feasibility test results. This can be proven through the results of product validity tests on media experts with a percentage of 94.44% which means very feasible, on material experts with a percentage of 88.75% which means very feasible, and validity tests based on small-scale student responses with a percentage of 85% which means very feasible. These results indicate that the development of this 3D drawing video tutorial can be used in learning. Based on the overall percentage gain from the results of the product feasibility validity test, it can be said that the 3D drawing video tutorial media displayed through the utilization of the google sites platform is considered feasible to use in learning.